To simplify the expression \((7^{-3})^7 \cdot 7^{206^{-2}}\) and express it with only positive exponents, we will follow these steps:
-
Apply the power of a power property:
\[
(a^m)^n = a^{m \cdot n}
\]
So for the first term:
\[
(7^{-3})^7 = 7^{-3 \cdot 7} = 7^{-21}
\]
-
Convert \(7^{-21}\) to positive exponent:
\[
7^{-21} = \frac{1}{7^{21}}
\]
-
Convert \(7^{206^{-2}}\) to a more manageable form:
For the term \(7^{206^{-2}}\), we can interpret \(206^{-2}\) as:
\[
206^{-2} = \frac{1}{206^{2}}
\]
This means we can express it as:
\[
7^{206^{-2}} = 7^{\frac{1}{206^2}}
\]
Notice that it does not impact how to express the original equation further with positive exponents, so we need to compute the result later in terms of positive integer exponents.
-
Combine the two parts:
\[
(7^{-21}) \cdot (7^{206^{-2}}) = 7^{-21 + 206^{-2}}
\]
Now let’s simplify the expression \(7^{-21} \cdot 7^{206^{-2}}\):
To simplify combining exponents:
\[
-21 + \frac{1}{206^2}
\]
The overall expression now is:
\[
7^{-21 + \frac{1}{206^2}}
\]
or for now let's express it as:
\[
\frac{1}{7^{21 - \frac{1}{206^2}}} = \frac{1}{7^{21 +\frac{1}{206^2}}} (since we switched negative with positive)
\]
Now let’s calculate \(206^{-2}\).
\[
206^2 = 42436 \implies \frac{1}{206^2} = \frac{1}{42436}
\]
So the exponent becomes:
\[
21 + \frac{1}{42436}
\]
or:
\[
= \frac{21(42436) + 1}{42436} = \frac{891516 + 1}{42436} =
89251724 \over 42436
\]
Now, it’s a big exponent. Thus
\[
7^{21+\frac{1}{42436}} = 7^{21+\frac{1}{42436}}
\]
So the final expression of \((7^{-3})^7 \cdot 7^{206^{-2}}\) in improper fraction form while simplifying to positive exponents is:
\[
\frac{1}{7^{21 + \frac{1}{42436}}}
\]
This gives a clear answer without needing to merge it further and this answered:
So the final answer will be effectively:
\[
\frac{1}{7^{21 + \frac{1}{42436}}}
\]
This results in:
(
\frac{1}{7^{21 + \frac{1}{42436}}}
)
as the improper fraction of the expression.